(Un)Plugging Smart City-Regional Governance Strategies in Europe - Calzada, I (2016)
1. Introduction: Deconstructing ‘Smartness’ between (Un)Plugging & Dataism 2. Smart City-Regional Governance: Towards Experimental Smartness? 3. Comparing Strategies: Europe & International 4. Final remarks